PERBANDINGAN METODE HUNGARIAN DAN PENDEKATAN PROGRAM DINAMIS DALAM PEMECAHAN ASSIGNMENT PROBLEM - Marpaung, Budi (Teknik dan Ilmu Komputer, 2012)
During this assignment problem can be solved only by the Hungarian method. Though highly effective approach to the dynamic program to solve the assignment problem. This paper describes a problem solving assignment for five machines and five jobs. The results showed that both methods give the same solution. Even the difficulty in precisely Hungarian Method can be helped by using a dynamic program approach.ÃÂ ÃÂ Keywords: assignment problem, Hungarian Method, dynamic programming, foreward recursive equation, backward recursive equation.